Solid cooking fuel use and cognitive decline among older Mexican adults. (24th April 2021) - Saenz, Joseph L.
ABSTRACT: Studies of air pollution and cognition often rely on measures from outdoor environments. Many individuals in low‐ and middle‐income countries are exposed to indoor air pollution from combustion of solid cooking fuels. Little is known about how solid cooking fuel use affects cognitive decline over time. This study uses data from the 2012, 2015, and 2018 Mexican Health and Aging Study ( n  = 14 245, age 50+) to assess how use of wood or coal for cooking fuel affects cognition of older adults relative to use of gas. It uses latent change score modeling to determine how using solid cooking fuel affected performance in Verbal Learning, Verbal Recall, Visual Scanning, and Verbal Fluency. Solid cooking fuel was used by 17% of the full sample but was more common in rural areas. Solid fuel users also had lower socioeconomic status. Compared to those using gas, solid fuel users had lower baseline scores and faster decline in Verbal Learning ( β  = −0.18, p  < 0.05), Visual Scanning ( β  = −1.00, p  < 0.001), and Verbal Fluency ( β  = −0.33, p  < 0.001). Indoor air pollution from solid cooking fuels may represent a modifiable risk factor for cognitive decline. Policy should focus on facilitating access to clean cooking fuels.